2017
DOI: 10.2147/ccide.s134125
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin modulates gingival cytokine and MMP production in a rat model of ligature-induced periodontitis

Abstract: PurposeThe aim of this study was to evaluate the effect of simvastatin on the synthesis of cytokines TNF-α and IL-10 and metalloproteinase (MMPs) 2 and 9 in a rat model of ligature-induced periodontitis.Materials and methodsTwenty Wistar rats were used, and a cotton ligature was place in a subgingival position encircling the entire cervix of the first molar of the left (ipsilateral) side of the mandible. The right (contralateral) side of the mandible had no ligature placed and was used as control. After the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…MMPs are critical in the degradation of the extracellular matrix composing the connective tissue attachment apparatus to roots, resulting in attachment loss in periodontitis . MMP‐9 in the gingival crevice and surrounding gingiva has been shown to be a primary diagnostic biomarker of human periodontitis, and SIM reduced MMP‐9 in gingiva of a rat ExP model similar to the current study . TNF‐α is a known potent inflammation‐induced osteoclastogenic cytokine .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…MMPs are critical in the degradation of the extracellular matrix composing the connective tissue attachment apparatus to roots, resulting in attachment loss in periodontitis . MMP‐9 in the gingival crevice and surrounding gingiva has been shown to be a primary diagnostic biomarker of human periodontitis, and SIM reduced MMP‐9 in gingiva of a rat ExP model similar to the current study . TNF‐α is a known potent inflammation‐induced osteoclastogenic cytokine .…”
Section: Discussionsupporting
confidence: 77%
“…(41) MMP-9 in the gingival crevice and surrounding gingiva has been shown to be a primary diagnostic biomarker of human periodontitis, (42) and SIM reduced MMP-9 in gingiva of a rat ExP model similar to the current study. (43) TNF-a is a known potent inflammation-induced osteoclastogenic cytokine. (44) TNF-a strongly promotes inflammatory osteolysis by stimulating activation of macrophages and osteoclast precursors and enhancing expression of osteoclastogenic cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Because the release of inflammatory factors was also essential for periodontitis occurrence, the effects of miR‐218 and Mmp9 on inflammatory response were assessed in this study. Periodontal tissues showed the increased production of Mmp9 in response to inflammatory factors, and Mmp9 played a vital role in the development and progression of inflammation (Balli et al, ; Mouchrek Junior et al, ; Tsai et al, ). Recent studies have suggested that miRNAs could regulate inflammatory cytokines and contribute to some cancers and inflammatory diseases (Yang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…As an FDA-approved medication, SIM has a fully established safety profile, which is superior to the BIO used in the previous study . Moreover, in our current in vivo efficacy study, the effective drug dose used was equivalent to 80 μg of SIM per week, which is much lower than the dosing level reported previously. , From the safety perspective, no abnormal body weight change, histological abnormality, or any abnormal behavior was observed during the study, supporting the safety of the formulation.…”
Section: Discussionmentioning
confidence: 99%